1981
DOI: 10.1002/chin.198107132
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: PHOTOREACTIVITY IN SOLUTION. PART 18. INTRAMOLECULAR PHOTOADDITION OF THE EXCITED CARBONYL GROUP OF CYCLOALKANONES TO A NONCONJUGATED ETHYLENIC DOUBLE BOND

Abstract: Allylcycloalkanone wie (I) ergeben unter Lichteinwirkung hauptsächlich die Oxetane (II) und (III), wobei das Produktverhältnis (II)/(III) zwischen 2:1 und 1:4 liegt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…Our findings resemble a report of Kossanyi et al concerning photoreactions of 2-allylcyclopentanone . The authors observed the formation of both crossed and straight oxetanes in nearly equal amounts.…”
Section: Resultssupporting
confidence: 92%
“…Our findings resemble a report of Kossanyi et al concerning photoreactions of 2-allylcyclopentanone . The authors observed the formation of both crossed and straight oxetanes in nearly equal amounts.…”
Section: Resultssupporting
confidence: 92%
“…In contrast, if 7-Cy is used as reaction vessel, the alkyl carbene to a significant amount may also insert into the O-H bonds of the host, [18] a process that also explains the low recovery of products after irradiation of 1b@7-Cy. But since TRIMEB does not possess functional groups or bonds which are susceptible to react easily with a relatively nucleophilic alkyl carbene, [7] 1a only can rearrange intramolecularly, affording endo-tricyclo[3.3.0.0 2,8 ]octan-3-ol (7a) [19] and bicyclo[3.3.0]oct-5-en-3-ol (6a) [20] in a ratio depending on the host molecule used. In the case of 1a@TRIMEB, the larger size of the cavity also allows a total separation of one guest molecule from another.…”
Section: Discussionmentioning
confidence: 99%
“…An intramolecular reaction on allyl cyclopentanone derivatives has been reported [227,252,253]. In this case both straight 37 and crossed 38 oxetanes can be obtained (Scheme 43).…”
Section: Intramolecular Reactionsmentioning
confidence: 99%
“…The reaction of biacetyl with benzvalene gave the corresponding adduct, while benzophenone gave, as the only product, benzene [44]. When homobenzvalene was used as the alkene in the reaction with ethyl phenylglyoxylate, the irradiation gave the corresponding adduct in 70% yield with high stereoselectivity (Scheme 39) [227].…”
Section: Other Intermolecular Reactionsmentioning
confidence: 99%